2015
DOI: 10.21608/jfds.2015.48857
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding at Different Levels of Wheat Bran and Date Seeds Powder on Diabetic Rats

Abstract: There is a global rise in the incidence of diseases like diabetes mellitus, atherosclerosis and cardiovascular diseases. Therefore, this study was designed to examine the effect of adding fine bran and date seeds powder as a sources of dietary fibers and active healthy components to prepare functional bread for lowering blood glucose and cholesterol levels. Sensory evaluation revealed that successful replacement of bread samples with 5,10 and 15% fine bran (Fb), 5 and 10% date seeds powder (Dsp) and the mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…In general, bread prepared with addition of DBRB was acceptable, but recorded lower scores than those of control bread. These results are in agreement with these obtained by Park et al, 1997;Hassan (2003) and Khalil et al, (2015), who reported that adding different sources of fibers in pan bread making decreased organoleptic properties.…”
Section: Minerals Content Of Black Rice and Black Rice Bransupporting
confidence: 93%
“…In general, bread prepared with addition of DBRB was acceptable, but recorded lower scores than those of control bread. These results are in agreement with these obtained by Park et al, 1997;Hassan (2003) and Khalil et al, (2015), who reported that adding different sources of fibers in pan bread making decreased organoleptic properties.…”
Section: Minerals Content Of Black Rice and Black Rice Bransupporting
confidence: 93%
“…In general, the bread and rusks that were made using Z. coccineum powder were considered acceptable, but they received lower ratings when compared to the control samples. These observations are supported by the study conducted by Khalil et al, (2015), where it was found that incorporating different types of fibers into the production of pan bread resulted in a decrease in its sensory properties.…”
Section: Dried (Zygophyllum Coccineum L) Powder … Essam El Sayed 99supporting
confidence: 65%
“…Following the administration of aqueous suspension of date seed for four weeks, glucose level was decreased in date seed-treated rats when compared to untreated rats (248.0 ± 42.0 mg/dL vs. 508.0 ± 60.0 mg/dL). Khalil et al [83] demonstrated that blood glucose level was significantly (p < 0.05) reduced from baseline (284.7 mg/dL vs. 172.5 mg/dL) following a 30-day administration with date seed powder (Zahdi variety) given in combination with fine bran to streptozotocin-induced diabetic rats. Furthermore, date seed supplementation at 5%,10%, and 15% can significantly reduce blood glucose levels in a concentration-dependent manner in male diabetic rats to 176.7 ± 11.0 mg/dL (p < 0.05), 130.7 ± 9.0 mg/dL (p < 0.01) and 121.1 ± 11.5 mg/dL (p < 0.001), respectively.…”
Section: Antihyperglycemic Activitymentioning
confidence: 99%